MicroRNA-1303 in cancer pathogenesis and therapy: clinical implications for biomarker development and targeted treatment strategies - Lingzi Zheng; Ling Hu; Bita Badehnoosh (Cancer Cell International)
Abstract Cancer remains one of the most formidable global health challenges due to its complex pathogenesis, late-stage diagnosis, and limited therapeutic options for many subtypes. Despite advancements in reducing cancer-related mortality through lifestyle modifications and early interventions, it continues to rank among the top ten causes of death worldwide. A growing body of evidence highlights the critical role of non-coding RNAs, particularly microRNAs (miRNAs), in cancer biology. MiRNAs are short, non-coding RNA molecules approximately 19–25 nucleotides in length that regulate gene expression at the post-transcriptional level. Among these, miRNA-1303 has garnered increasing attention due to its aberrant expression across a variety of malignancies and its involvement in diverse cellular processes, including cell proliferation, apoptosis, migration, invasion, and chemoresistance. In this review, we provide a comprehensive overview of miRNA-1303, emphasizing its dysregulation in different cancer types such as colorectal, breast, prostate, and lung cancers. We explore the molecular mechanisms and signaling pathways modulated by miRNA-1303, including its interaction with oncogenes, tumor suppressors, and key cellular networks like PI3K/AKT, Wnt/β-catenin, and MAPK pathways. We also discuss its functional role in tumor development and progression, supported by both in vitro and in vivo studies. Furthermore, we evaluate the potential of miRNA-1303 as a clinically relevant biomarker for early cancer detection, prognosis prediction, and treatment monitoring. Its expression patterns have been correlated with tumor stage, metastasis, and patient survival, suggesting promising utility in clinical decision-making. In addition, we explore the emerging therapeutic strategies targeting miRNA-1303, including miRNA mimics, inhibitors, and delivery systems designed to modulate its expression in cancer cells. By synthesizing current findings, this review underscores the clinical significance of miRNA-1303 in oncology and proposes future directions for its application in personalized medicine.